Detecting Financial Statement Fraud in Public Sector Institutions: Insights from Internal Auditors in Law Enforcement Organizations - Ramadhan, Eko; Jatmiko, Tri (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to explore the role of auditors in detecting fraudulent financial statements within police agencies, particularly at the Regional Police (POLDA) level. Using a qualitative approach with an interpretive paradigm and phenomenological methods, this study examines the experiences of internal auditors from the Regional Supervisory Inspectorate (Itwasda) in dealing with the dynamics of public sector financial oversight. Data were collected through semi-structured interviews and audit document analysis. The results indicate that the role of auditors is not limited to detection functions but also encompasses fraud prevention and response through a risk-based approach and cross-institutional collaboration. Key challenges include limited access to information, bureaucratic complexity, and potential conflicts of interest within the organizational structure. This study enriches the forensic accounting literature by presenting a contextual perspective from the public sector and reaffirms the relevance of Responsive Regulation theory in audit practice.